Symptoms of Acute Posttraumatic Stress Disorder in Prostate Cancer Patients Following Radical Prostatectomy - Ioannis Anastasiou MD; Konstantina G. Yiannopoulou MD; Anastasios Mihalakis MD; Nikolaos Hatziandonakis MD; Constantinos Constantinides MD, PhD; Charalambos Papageorgiou MD, PhD; Dionisios Mitropoulos MD, PhD (American Journal of Men's Health, 2011)
Psychological morbidity is increasingly reported in cancer survivors. The authors’ objective was to determine the presence of acute posttraumatic stress disorder (PTSD) symptoms in prostate cancer (PC) patients following radical prostatectomy. Fifteen patients who underwent radical prostatectomy for localized prostate cancer were assessed for the presence of PTSD-related symptoms by completing the Davidson Trauma Scale (DTS), a month following the procedure. A group of 20 patients who underwent surgery for benign prostate hyperplasia (BPH) served as the control group. PTSD total scores were significantly higher in PC patients when compared with BPH patients, whose PTSD scores did not differ from those reported in the general population (32.6 ± 18.5 vs. 11.3 ± 9.7, p = .001) . PTSD did not vary among PC patients when adjusted for educational status. PTSD symptoms are common among patients undergoing radical prostatectomy and independent of their educational level. Research investigating these aspects of posttreatment psychological adjustment is needed for developing well-targeted psychological interventions.